Application of Two Delay Differential Equations in the Evolutionary Game of Public Goods Supply. (21st September 2022) - Sun, Simo; Man, Wang; Yang, Hui
Abstract : Starting from the leading role of public goods suppliers' supply strategies, the government's incentives and support to suppliers, and consumers' influence on public opinion and other factors, the matrix game models between public goods suppliers and between the suppliers and the government are established, respectively. Considering the delay of government and supplier strategies, establish two delay differential equations between the two suppliers and between the supplier and the government, obtain the evolutionary game model of public goods supply, and solve the equilibrium point of the evolutionary game model with or without delay and its stability. Then, through model parameter analysis, verify the rationality of public goods supplier's supply and government incentive strategy. Finally, through numerical simulation, it is verified that the delay does not affect the stability of the equilibrium point of the game party but changes the rate at which the game party's strategy reaches a steady state, conducive to rapid, scientific, and reasonable decision-making between the suppliers of public goods and between the government and suppliers.